Entrepreneurial stock brokering and switching cost - G. Geoffrey Booth; Orkunt M. Dalgic; Juha-Pekka Kallunki; Petri Sahlström (The Journal of Entrepreneurial Finance and Business Ventures, 2007)
Stock brokers are entrepreneurs who incur switching costs when the change brokerage houses. We use Helsinki Stock Exchange data to investigate these costs by examining whether investors are loyal to their brokers when brokers move. We find that investors who have extant relationships with the new house are more likely to switch with them. New houses that are less active in a particular stock are more likely to attract the investors from the old houses, and savvy (knowledgeable) investors are more likely to stay with their broker.
Keywords: 650